An ultrasensitive electrochemical enzymatic urea biosensor based on aniline/nbutyl acrylate conducting polymer-modified screen-printed electrode - Ulianas, Alizar; Sharina Abu Hanifah,; Ling, Ling Tan; Normazida Rozi,; Lee, Yook Heng; Ling, Ling Tan; Dewata, Indang; Mawardi, Mawardi; Yulkifli,; Zainul, Rahadian; Yuniarti, Elsa; Suryani, Okta; et al. (Penerbit Universiti Kebangsaan Malaysia, 2024)
An enzymatic electrochemical biosensor for urea detection was developed using the succinimide-modified aniline/n-butyl acrylate (nBA) conducting polymer. This aniline/nBA conducting polymer was synthesized by photopolymerization with the succinimide moiety incorporated during the photocuring procedure. The urease enzyme originating from Jack beans was chemically grafted on the succinimide-functionalized aniline/nBA conducting polymer, which was attached to a screen-printed carbon paste electrode (SPE). The enzymatic hydrolysis of urea by the urease electrode diminished the voltammetric biosensor response as a result of the cascaded chemical reaction between the enzymatically hydrolyzed hydroxide (OH- ) ion and the K3 Fe(CN)6 redox species that generating the side products (Fe(OH)3 , CN- ion, and KCN), which impeded the electron transfer of the redox mediator at electrodeelectrolyte interface. In view of the amount of side products produced was proportional to the urea concentration associated in the enzymatic reaction with the immobilized urease enzymes, this has allowed the proposed enzymatic biosensor to demonstrate an inverse sensitivity concept of detecting urea concentration in an ultrasensitive manner. The electron transfer rate constant (k) of the urease electrode based on aniline/nBA hybrid material at the electrodeelectrolyte interface was determined at 5.374×10-5 cm s-1. The linear response range of the enzymatic urea biosensor was obtained from 1×10-10 mM to 1×10-1 mM (R2 =0.9834) by differential pulse voltammetry (DPV) with a limit of detection of 4.72×10-11 mM at pH 5.0 and enzymatic hydrolysis time of 30 min. The voltammetric urea biosensor response showed good reproducibility with a promising relative standard deviation (RSD) acquired at 5.0% (n=9). The ultra-high sensitivity performance of the developed enzymatic biosensor based on aniline/nBA conducting polymer towards determination of urea concentrations at low levels has demonstrated superior performance across previously reported electrochemical urea biosensors based on various nanostructured conducting materials.